ANALISIS PENGARUH PEMBERDAYAAN DAN MODAL SOSIAL TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL ( Studi pada DPPKAD Kabupaten Batang ) (Students' Journal of Economic and Management, 2012)
Purpose of execution of this study was to examine and analyze the effect of empowerment on organizational commitment, the influence of social capital on organizational commitment, empowerment influence on employee performance, the influence of social capital on the performance of employees, the influence of organizational commitment to employee performance, empowering effect on the performance of employees with a commitment to mediation organizational and social capital influence on employee performance with organizational commitment mediated The research was conducted at the Department of Finance and Asset Management Revenue District Trunk numbering 87. Sampling technique using census. The test results I obtained the results of the regression equation Adjusted R Square of 0.734, meaning that the change of variables oragnisasional commitment can be explained by the variables of empowerment and social capital by 73.4%, while for the test results obtained equation II Adjusted R Square of 0.857, meaning that the changes of the variable employee performance can be explained by the variable empowerment, social capital and organizational commitment of 85.7% Based on the known partial regression testing empowerment affect organizational commitment with significance 0.000 <0.05, the social capital of the organizational commitment to the significance 0.000 <0.05, empowering effect on performance with significance 0.013. <0.05, effect of social capital on the performance of the significance 0.009. <0.05 and commitment affect organizational performance with significance 0.000. <0.05. It is identified that all the hypotheses accepted or proven. Testing mediation empowerment on employee performance with organizational commitment mediation showed that the indirect effect is greater than the direct effect (0.232> 0.196). While social capital on employee performance with organizational commitment mediation showed that the indirect effect is greater than the direct effect (0.283> 0.214). It identifies that organizational commitment is a mediating variable. Key word         : Empowerment, Social Capital, Organizational Commitment and Employee Performance